2020
DOI: 10.1002/pen.25546
|View full text |Cite
|
Sign up to set email alerts
|

Re‐entrant auxetic structures fabricated by fused deposition modeling: An experimental study of influence of process parameters under compressive loading

Abstract: The present article is focused on investigating the influence of process parameters under compressive loading in case of reentrant auxetic structures fabricated by fused deposition modeling (FDM). Auxetic structures of acrylonitrile butadiene styrene (ABS) and poly‐lactic acid (PLA) materials are fabricated. Three process parameters of FDM namely layer thickness, raster angle, and number of contours are considered to investigate their influence on compressive strength, stiffness, and specific energy absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…This relative difference between the loading direction and build direction results in different mechanical behavior of structures with variation of layer height. Similar trend is observed by Vyavahare et al [ 33 ] while performing compression testing on re‐entrant auxetic structures of ABS and PLA material.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This relative difference between the loading direction and build direction results in different mechanical behavior of structures with variation of layer height. Similar trend is observed by Vyavahare et al [ 33 ] while performing compression testing on re‐entrant auxetic structures of ABS and PLA material.…”
Section: Resultssupporting
confidence: 84%
“…They found that extrusion temperature significantly affects the strength of the part. Vyavahare and Kumar [ 33 ] investigated the influence of layer height, line direction, and number of shells on strength of re‐entrant structures made of ABS and PLA. They reported that the strength of the structure proportionately varies with the change in layer height.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric 3D auxetics have been achieved, for example, using fused-deposition modelling (FDM) [75], which is low-cost and highly interesting for biomedical applications as several PLA, PCL and TPU medical grade printing filaments are already available.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…The feasibility of FDM producing vertical structural components with the help of support structures has made it the method of choice for experimentation of such structures at minimal costs. Such structures have demonstrated a parabolic relationship between the Poisson's ratio and its re-entrant angle when analyzed experimentally [75,76]. Because the material is highly anisotropic, the properties of the parent materials seem to have a dominant effect on the auxetic behavior of the composites.…”
Section: Fdmmentioning
confidence: 99%